2007
DOI: 10.1111/j.1471-0528.2007.01443.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of surgically trained assistant medical officers in performing major obstetric surgery in Mozambique

Abstract: Objective To compare the training and deployment costs and surgical productivity of surgically trained assistant medical officers (te´cnicos de cirurgia) and specialist physicians (surgeons and obstetrician/gynaecologists) in Mozambique in order to inform health human resource planning in a developing country with low availability of obstetric care and severe physician shortages. Te´cnicos de cirurgia have been previously shown to have quality of care outcomes comparable to physicians.Design Economic evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
110
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 16 publications
3
110
0
Order By: Relevance
“…Numerous published reports have shown that abbreviated surgical training programs are successful and cost-effective interventions to expand the supply of surgical services in LMICs [27][28][29]. World Health Organization-CHOosing Interventions that are Cost-Effective (WHO-CHOICE) has established the threshold for cost-effective programs as less than three times the gross domestic product per capita per DALY averted and the threshold for highly cost-effective programs as less than the gross domestic product per capita per DALY averted.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous published reports have shown that abbreviated surgical training programs are successful and cost-effective interventions to expand the supply of surgical services in LMICs [27][28][29]. World Health Organization-CHOosing Interventions that are Cost-Effective (WHO-CHOICE) has established the threshold for cost-effective programs as less than three times the gross domestic product per capita per DALY averted and the threshold for highly cost-effective programs as less than the gross domestic product per capita per DALY averted.…”
Section: Discussionmentioning
confidence: 99%
“…In Mozambique, cost per major obstetric surgery for TCs was $39 versus $144 for obstetricians/gynecologists [181]. In Burkina Faso, the estimated average cost per averted newborn death for an obstetrician-led team compared with a general practitioner-led team was 11 757 international dollars (due largely to personnel availability and larger teams in urban settings), and 200 international dollars for a general practitioner-led team versus a clinical officer-led team.…”
Section: Evidence Regarding Cost-effectivenessmentioning
confidence: 99%
“…Already in some countries such as Tanzania, Malawi, Mozambique and the Democratic Republic of Congo, scarce specialists train nonphysicians and nurses in surgical and perioperative skills (Longombe 1997;Kruk et al 2007;Lavy et al 2007). This commentary draws on the experiences of the authors in Uganda, including a full career of surgical practice and education (SL), as well as the published and 'grey' literature, to describe how and why this 'recasting' could occur.…”
Section: Rethinking the Role Of Surgery In Public Healthmentioning
confidence: 99%